The neurobiology of obsessive-compulsive disorder : neuroanatomy, neurochemistry, and pharmacotherapy - Stein, Dan J. (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--Stellenbosch University, 2001.